Government Insurance Against Natural Disasters : An Application to the ECCU - Guerson, Alejandro (IMF Working Papers; Working Paper ;, 2020)
This paper estimates insurance requirements against natural disasters (NDs) in the Eastern Caribbean Currency Union (ECCU) using an insurance layering framework. The layers include a government saving fund, as well as market instruments. Each layer is calibrated to cover estimated fiscal cost of NDs according to intensity and expected damage. The results indicate that ECCU countries could target saving fund stocks for relativelly smaller and more frequent events in the range of 6-12 percent of GDP, enough to cover 95 percent of NDs' fiscal costs. To ensure financially-sustainable saving funds with a low probability of depletion, this requires annual budget savings in the range os 0.5 to 1.9 percent of GDP per year. Additional coverage could be obtained with market instruments for large and less frequent events, albeit at a significant cost.The results are based on a Monte-Carlo experiment that simulates natural disaster shocks and their impact on output and government finances.